`int x^3sinx dx` Find the indefinite integral

Expert Answers

An illustration of the letter 'A' in a speech bubbles

Recall that indefinite integral follows `int f(x) dx = F(x) +C` where:

`f(x)` as the integrand function

`F(x)` as the antiderivative of ` f(x)`

`C` as the constant of integration.

 For the given  integral problem: `int x^3 sin(x) dx` , we may apply integration by parts: `int u *dv = uv - int v *du` .

Let:

`u = x^3`  then `du =3x^2 dx`

`dv= sin(x) dx` then `v = -cos(x)`

Note: From the table of integrals, we have `int sin(u) du = -cos(u) +C` .

Applying the formula for integration by parts, we have:

`int x^3 sin(x) dx= x^3*(-cos(x)) - int ( -cos(x))* 3x^2dx`

                               `= -x^3cos(x)- (-3) int x^2*cos(x) dx`

                               `=-x^3cos(x)+3 int x^2 *cos(x) dx`

Apply another set of integration by parts on `int x^2 *cos(x) dx` .

Let:

`u = x^2` then `du =2x dx`

`dv= cos(x) dx` then `v =sin(x)`

Note: From the table of integrals, we have `int cos(u) du = sin(u) +C` .

Applying the formula for integration by parts, we have:

`int x^2 cos(x) dx= x^2*(sin(x)) - int sin(x) * (2x) dx`

                              ` = x^2sin(x)- 2 int x*sin(x) dx`

                             `= x^2sin(x)-2 int x *sin(x) dx`

Apply another set of integration by parts on `int x *sin(x) dx` .

Let: `u =x` then `du =dx`

       `dv =sin(x) dx` then `v =-cos(x)`

Note: From the table of integrals, we have `int sin(u) du =-cos(u) +C` .

`int x *sin(x) dx = x*(-cos(x)) -int (-cos(x)) dx`

                              `= -xcos(x) + int cos(x) dx`

                              `= -xcos(x) + sin(x)`

Applying `int x *sin(x) dx =-xcos(x) + sin(x)` , we get: 

`int x^2 cos(x) dx=x^2sin(x)-2 int x *sin(x) dx`

                               `= x^2sin(x)-2 [-xcos(x) + sin(x)]`

                                `=x^2sin(x)+2xcos(x) -2sin(x)` .

 Applying `int x^2 cos(x) dx=x^2sin(x)+2xcos(x) -2sin(x)` , we get the complete indefinite integral:

`int x^3 sin(x) dx=-x^3cos(x)+3 int x^2 *cos(x) dx`

                               `=-x^3cos(x)+3[x^2sin(x)+2xcos(x) -2sin(x)] +C`

                               `=-x^3cos(x)+ 3x^2sin(x) +6xcos(x) - 6sin(x) +C`

 

See eNotes Ad-Free

Start your 48-hour free trial to get access to more than 30,000 additional guides and more than 350,000 Homework Help questions answered by our experts.

Get 48 Hours Free Access
Approved by eNotes Editorial